PENGARUH PENDIDIKAN KESEHATAN MELALUI METODE PEER GROUP TERHADAP KETERAMPILAN TENTANG PERAWATAN LUKA DAN BIDAI PADA SISWA - Iqbal, Muhammad Al; Riza, Saiful; Mulfianda, Riyan (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Literature studies show that the incidence of accidents and joint dislocations in students is still high, with 6 - 10 cases occurring at school. This continues to be a concern for schools so that the school health unit (UKS) has an important role in first aid for accidents (P3K). in schools. So efforts are needed to increase students' understanding with various educational and evaluation methods related to First Aid. The aim of the research is to look at differences in health education through the peer group method on skills regarding wound care and splints among students. This research uses a Quasy Experiment design. The sample in this study used a purposive sampling technique based on criteria with a sample size of 60 respondents divided into two groups, namely 30 intervention groups and 30 control groups. The measuring tools used are SOP Wound Care Splints and Observation Sheets. The time for conducting the research was September 10-13 2024. Data were analyzed using the Shapiro Wilk Test & Paired T Test. The results of the research in the intervention group were differences in skills regarding wound care and splints among students before and after being given health education through the peer group method at SMP N 2 Mesjid Raya with a value of p = 0.000, and in the control group there were differences in skills regarding wound care and splints. Students at PKPU Aceh Middle School with a value of p = 0.000. The conclusion in this study is that there is a comparison between the intervention group and the control group regarding skills regarding wound care and splints in students with a value of p = 0.043. It is hoped that the School Health Unit and Community Health Center can provide health education to students through collaboration on various first aid cases.